Optimal energy scheduling of a standalone rural microgrid for reliable power generation using renewable energy resources. Issue 1 (31st December 2023) - Kamal, Md Mustafa; Asharaf, Imtiaz; Fernandez, Eugene
ABSTRACT: Rural villages can be electrified using renewable power sources for the area to grow effectively. Microgrids powered by renewable energy is more environmentally friendly and practical choices for electrifying rural areas. This study attempts to ascertain the technological and financial viability of an autonomous hybrid energy source for a remote Indian area in order to provide a reliable power supply. The region's load requirements can be met with the help of a solar energy system, biogas, wind energy, diesel generators, and batteries. Differential evaluation (DE) is used to optimize the proposed microgrid for grid-independent operation. The system's ultimate objective is to reduce energy costs and recommend workable component configurations. Particle swarm optimization (PSO) and the genetic algorithm (GA) are used to compare the DE findings. The finding suggested the optimal energy cost of 0.22 /kWh, a net current cost of 5, 18, 656, and a capital cost of 8, 50, 774. DE's total net present cost is 4.3% less than PSO and 5.2% less than GA. However, it has been determined that the recommended approach is more practical and affordable for electrifying rural areas.